Occurrence of temperature spikes at a wetting front during spontaneous imbibition - Hamed Aslannejad (Nature Portfolio, 2017)
Abstract It is reported that temperature rises at wetting front during water infiltration into soil. The temperature goes back to the background value after passage of water front. Different explanations have been provided for source of energy causing temperature spike. Some have contributed it to heat of condensation released due to condensation of vapor on “dry” solid surface. Some other stated that the heat of wetting or heat of adsorption is responsible for the temperature rise. In this research, we revisited this issue. First, we provide a comprehensive review about occurrence of temperature spike at a wetting front. Then, we report about experiments we performed on the rise of water in dry paper. Using infrared and optical imaging techniques, we could monitor temperature changes in time and space. For all samples maximum temperature rise occurred at the wetting front. The magnitude of temperature spike depended on paper material, thickness, and liquid composition. It was larger for cellulose-fiber-based paper than for plastic-based paper. For a given paper type, thicker samples showed a larger temperature spike. Adding salt to the water caused reduction of temperature spike. It was concluded that replacement of air-solid interface with water-solid interface releases energy, which causes temperature rise.